Global pressure - Nordic solutions? The Nordic globalization barometer 2008 - Nordic Council of Ministers, Copenhagen; Ketels, Christian (Copenhagen, 2008)
"The Nordic region is prosperous – all Nordic countries have higher levels of prosperity than the average OECD-country. Only the United States and Ireland have a higher GDP per capita than the Nordic countries. However, even though we are successful now one important question remains: how can the Nordic countries also in the future continue to be competitive on a global scale?